Allergic Rhinitis and Depression: Profile and Proposal - Mou, Ya-Kui; Wang, Han-Rui; Zhang, Wen-Bin; Zhang, Yu; Ren, Chao; Song, Xi-Cheng (Frontiers in Psychiatry, 2022)
In addition to nasal symptoms, patients with allergic rhinitis (AR) often experience mental and psychological disorders such as depression. Depression not only makes the treatment of AR more difficult and expensive but also poses a serious impact on the patients' daily activities and quality of life, thus bringing additional burden to the families and the society. Here we systematically review the recent research advances in the correlation between AR and depression, analyze the possible causes and mechanisms of depression in AR, summarize the current diagnosis and treatment strategies, and provide our insights into the AR-related depression; in addition, we introduce briefly the basic research status on AR-related depression. We hope that this review article will provide evidence for future studies.